2021
DOI: 10.1002/nop2.986
|View full text |Cite
|
Sign up to set email alerts
|

Associations between heteronormative information, parental support and stress among same‐sex mothers in Sweden—A web survey

Abstract: New legislation and access to assisted reproduction technologies have led to an increased number of same-sex mothers (McManus et al., 2006). In 2005, female couples gained access to assisted reproduction at Swedish clinics (Socialstyrelsen, 2005). Since 2009, when same-sex marriage was allowed in Sweden, 3600 female couples have married (Statistics Sweden, 2018). These legislations probably contribute to a variety of diverse family constellations and parental roles. Professional antenatal care is included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…All participants expressed that it goes without saying that they should include and support both parents, even though some participants said they supported the birth mother the most. Previous research found that non‐birth mothers experienced less support from health care professionals than birth mothers [9] underlining that health care professionals need to expand their support to include the whole family. Professionals in antenatal and child health care have an important task in providing culturally respectful care [1, 2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All participants expressed that it goes without saying that they should include and support both parents, even though some participants said they supported the birth mother the most. Previous research found that non‐birth mothers experienced less support from health care professionals than birth mothers [9] underlining that health care professionals need to expand their support to include the whole family. Professionals in antenatal and child health care have an important task in providing culturally respectful care [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reviews show that same‐sex mothers face heteronormative assumptions and insufficient affirmation and support within antenatal and child health care [6, 12, 13]. Same‐sex mothers experience the transition to parenthood as stressful and parental groups in antenatal and child health care as not very supportive, and non‐birth mothers lack sufficient support in their transition to parenthood [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Swedish society can be regarded as progressive, research on mothers in same-sex partnerships has indicated similar issues of exclusion, with additional concerns of heteronormative assumptions. Nonbirthing mothers highlight the need for acknowledgment of being a parent in their own right (Dahl & Malterud, 2015; Wells & Lang, 2016) and report lower parental support (Appelgren Engström et al, 2022). Similar to single mothers, same-sex parents have received little attention in the COVID-19 literature in Sweden, but Naurin et al (2021) found that nonbirthing parents in general experienced increased worry for their pregnant partner and unborn child, especially those with a lack of trust in health care.…”
Section: Theoretical Basis Of Parenting Adjustmentmentioning
confidence: 99%